2020
DOI: 10.1111/1467-8551.12424
|View full text |Cite
|
Sign up to set email alerts
|

What is (s)he Worth? Exploring Mechanisms and Boundary Conditions of the Relationship Between CEO Extraversion and Pay

Abstract: Integrating human capital theories and the status incongruity hypothesis at the upper echelons, we examine for whom extraversion, the personality trait that has been most strongly and consistently implicated in leader success, influences Chief Executive Officer (CEO) pay. To assess the personality traits of CEOs, we used a computerized text analysis approach on the language spoken by CEOs in conference calls. Using a sample of firms listed on the S&P 1500, we find that more extraverted CEOs earned higher pay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 91 publications
2
5
1
Order By: Relevance
“…Second, our results challenge one of tokenism theory's key tenet that better outcomes result when minority groups gain representation, revealing that that greater female representation on boards can sometimes be related to greater gender‐based disparities. Our findings stand in contrast to prior research, which tends to find that greater female representation on the board is generally related to less gender bias in organizations (e.g., Abebe & Dadanlar, 2019), including toward female CEOs (e.g., Malhotra et al, 2020; Oliver et al, 2018). Even when prior work has found that greater female representation on the board was insufficient to engender positive or desired outcomes (e.g., Cook et al, 2019), it generally does not find it to be harmful for equality.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Second, our results challenge one of tokenism theory's key tenet that better outcomes result when minority groups gain representation, revealing that that greater female representation on boards can sometimes be related to greater gender‐based disparities. Our findings stand in contrast to prior research, which tends to find that greater female representation on the board is generally related to less gender bias in organizations (e.g., Abebe & Dadanlar, 2019), including toward female CEOs (e.g., Malhotra et al, 2020; Oliver et al, 2018). Even when prior work has found that greater female representation on the board was insufficient to engender positive or desired outcomes (e.g., Cook et al, 2019), it generally does not find it to be harmful for equality.…”
Section: Discussioncontrasting
confidence: 99%
“…We speculate that one possible explanation for this negative relationship could be because being a member of a greater number of external boards could be seen as a power‐seeking behavior, and a perceived desire for power tends to be punished in women, but not in men (e.g., Okimoto & Brescoll, 2010). Thus, beyond viewing these social connections as not as useful and valuable as those held by male CEOs, female CEOs may be further penalized by boards and compensation committees for being “power hungry.” Such an effect would be in line with the status incongruity hypothesis (Rudman & Phelan, 2008) and emerging evidence that boards can be negatively affected by gender stereotypes when determining the compensation of female CEOs (Malhotra et al, 2020).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…4.1). The low representation and the unadjusted pay gap suggest that women continue to experience lower board acceptance and are inhibited by the glass ceiling (Bertrand and Hallock 2001;Hendrix 2011;Malhotra et al 2021). Based on human capital theory, compensation research argues that lower pay is attributable to lower human capital (e.g., educational background and work experience).…”
Section: Introductionmentioning
confidence: 99%